Coating slurry for tarpaulin and composite tarpaulin

By combining water-based acrylate polyurethane, acrylic polymer monomer, flame retardant modified polymer and modified magnesium-aluminum hydrotalcite, a green and environmentally friendly tarpaulin coating slurry was developed, which solved the problem of insufficient flame retardancy of tarpaulin in the prior art, and achieved good flame retardant performance and infrared stealth effect.

CN119708992APending Publication Date: 2025-03-28SUNSHINE HEALTH MEDICAL TECH JIANGYIN CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411963531.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the prior art, the flame retardancy of tarpaulins is ignored, resulting in the inability to effectively protect the safety of equipment and personnel in flammable and explosive places, and it is difficult to take into account both stealth performance and flame retardancy.

Method used

By combining aqueous acrylate polyurethane, acrylic polymer monomer, flame retardant modified polymer and modified magnesium-aluminum hydrotalcite, a green and environmentally friendly tarpaulin coating slurry is developed to optimize the flame retardant performance and infrared stealth effect of the tarpaulin and improve the adhesion firmness.

Benefits of technology

It achieves good flame retardant performance and infrared stealth effect of the tarpaulin, while ensuring the firm adhesion of the coating, improving the safety and stealth performance of the tarpaulin in flammable and explosive places.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005217774680000091
    Figure BDA0005217774680000091
Patent Text Reader

Abstract

The invention discloses coating slurry for tarpaulin. The coating slurry comprises waterborne acrylate polyurethane, an acrylic polymeric monomer, a flame retardant modified polymer, modified magnesium-aluminum hydrotalcite, an emulsifier, an initiator and first deionized water, the flame retardant modified polymer is prepared from first polyisocyanate and first polyol through catalytic polymerization, and the first polyol comprises hydroxyl-terminated unsaturated polyether and a hydroxyl-containing flame-retardant monomer. The coating slurry for the tarpaulin is green and environment-friendly, and by compounding the waterborne acrylate polyurethane, the acrylic polymeric monomer, the flame retardant modified polymer and the modified magnesium-aluminum hydrotalcite, the flame retardant property of the tarpaulin is optimized, the infrared stealth effect is achieved, and the adhesion firmness with the tarpaulin is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer materials technology, specifically to a coating paste for tarpaulins and a composite tarpaulin. Background Technology

[0002] As a general-purpose piece of equipment, tarpaulins are widely used on ground military targets, such as military tents, tank shields, artillery covers, weapon covers, and the concealment of numerous fixed military targets. This requires tarpaulins to not only provide wind, dust, and rain protection, but also stealth capabilities. Flame retardancy is another crucial property of tarpaulins; good flame retardancy better ensures the safety of equipment and personnel, especially in flammable and explosive environments where high flame retardancy is required. However, current research on tarpaulins focuses primarily on improving their stealth performance, neglecting their flame retardancy. Developing a tarpaulin that combines stealth and good flame retardancy is a pressing problem in this field.

[0003] Therefore, it is necessary to improve the tarpaulin in the existing technology. Summary of the Invention

[0004] One of the objectives of this invention is to overcome the deficiencies in the existing technology and provide a green and environmentally friendly coating paste for tarpaulins. By compounding water-based acrylic polyurethane, acrylic polymer monomers, flame retardant modified polymers, and modified magnesium-aluminum hydrotalcite, the flame retardant performance of the tarpaulin is optimized, infrared stealth effect is achieved, and adhesion to the tarpaulin is strengthened.

[0005] To achieve the above-mentioned process effects, the technical solution of the present invention is as follows: a coating slurry for tarpaulins, comprising water-based acrylic polyurethane, acrylic polymer monomers, flame retardant modified polymers, modified magnesium-aluminum hydrotalcite, emulsifiers, initiators, and first deionized water;

[0006] The flame retardant modified polymer is prepared by catalytic polymerization of a first polyisocyanate and a first polyol, wherein the first polyol comprises a hydroxyl-terminated unsaturated polyether and a hydroxyl-containing flame retardant monomer.

[0007] The preferred technical solution is as follows: by mass parts, the coating slurry comprises 100 parts of waterborne acrylic polyurethane, 15-20 parts of acrylic polymer monomers, 10-15 parts of flame retardant modified polymer, 10-15 parts of modified magnesium-aluminum hydrotalcite, 2-4 parts of emulsifier, 1-2 parts of initiator, and 100-150 parts of first deionized water.

[0008] The preferred technical solution is as follows: the waterborne acrylate polyurethane is prepared from a second polyol, a second polyisocyanate, alcohol and / or amine small molecule chain extenders, hydrophilic chain extenders, double bond end-capping agents, salt-forming agents, and second deionized water, wherein the second polyol is one or more of polytetrahydrofuran diol, poly(ε-caprolactone diol), and polycarbonate diol.

[0009] The preferred technical solution is that the double bond end-capping agent is hydroxyethyl methacrylate, and the grafting content of the double bond end-capping agent in the waterborne acrylate polyurethane is 40% to 45%.

[0010] The preferred technical solution is that the hydroxyl-containing flame retardant monomer is synthesized from 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) and 4,4'-dihydroxybenzophenone (DHBP).

[0011] The preferred technical solution is that the molar ratio of the terminal hydroxyl unsaturated polyether to the hydroxyl-containing flame retardant monomer is (0.5~0.8):1.

[0012] The preferred technical solution is as follows: the modified magnesium-aluminum hydrotalcite is a layered intercalated hydrotalcite compound with olefinic unsaturated groups, and the magnesium-aluminum hydrotalcite matrix in the modified magnesium-aluminum hydrotalcite is prepared by magnesium salt, aluminum salt, sodium alginate and basic alcohol compound in a mass ratio of (1.5~2.5):1:(0.05~0.06):(45~50).

[0013] The preferred technical solution is that the acrylic polymer monomers include isooctyl acrylate, methyl methacrylate and 4-acryloylmorpholine in a mass ratio of (70-80):(3-5):(3-5).

[0014] The preferred technical solution is as follows: the emulsifier is one or more of octylphenol polyoxyethylene ether (OP-10), Span, Tween, and sodium 12-alkyl sulfonate, and the initiator is an aqueous solution of potassium persulfate and / or ammonium persulfate.

[0015] A second objective of this invention is to overcome the deficiencies in the prior art and provide a composite tarpaulin, comprising a substrate layer having a first surface and a second surface opposite each other along the layer thickness. A functional coating is disposed on the first surface and / or the second surface, the functional coating being obtained by drying the aforementioned tarpaulin coating paste. The substrate layer of the tarpaulin is a synthetic fiber or blended canvas, further comprising one or a blend of polypropylene fiber, ultra-high molecular weight polyethylene fiber, polyester fiber, polyester fiber, and nylon fiber. Further, the thickness of the functional coating is 120–150 μm.

[0016] The advantages and beneficial effects of this invention are as follows:

[0017] The coating paste used for this tarpaulin is a water-based, environmentally friendly material.

[0018] By compounding water-based acrylate polyurethane, acrylic polymer monomers, flame retardant modified polymers, and modified magnesium-aluminum hydrotalcite, the flame retardant properties of the tarpaulin are optimized, achieving infrared stealth effects and strong adhesion to the tarpaulin. Detailed Implementation

[0019] The specific embodiments of the present invention will be further described below with reference to examples. These examples are only used to more clearly illustrate the technical solutions of the present invention and should not be construed as limiting the scope of protection of the present invention.

[0020] Waterborne acrylic polyurethane

[0021] The second polyol is one or more of polytetrahydrofuran diol, poly(ε-caprolactone diol), and polycarbonate diol. Polytetrahydrofuran diol can increase the viscosity of polyurethane and has excellent properties such as low-temperature resistance, water resistance, oil resistance, abrasion resistance, and mildew resistance. Polyurethane materials synthesized from poly(ε-caprolactone diol) maintain good elasticity at lower temperatures and retain their physical properties at higher temperatures, exhibiting high hydrolysis resistance, low emulsion viscosity, and good strength, elasticity, and abrasion resistance. Polyurethane materials synthesized from polycarbonate diol possess good mechanical tensile properties, water resistance, heat resistance, aging resistance, and abrasion resistance.

[0022] The second polyisocyanate is isophorone diisocyanate (IPDI). IPDI has two different types of -NCO groups with different group activities, which can control the reaction conditions. The second polyol selectively reacts with the -NCO at the primary position of the aliphatic group to form a -NCO-terminated polyurethane prepolymer. The synthesized polyurethane material has excellent optical stability and chemical resistance.

[0023] Small molecule chain extenders increase the molecular chain length and molecular weight of oligomeric prepolymers. These chain extenders are small alcohol molecules, specifically one or more of ethylene glycol, propylene glycol, 1,4-butanediol, and trimethylolpropane. They are typically added during the prepolymer preparation stage to initiate the chain extension reaction. Using small molecule alcohols for chain extension reduces chain segment flexibility and increases the hardness of waterborne polyurethane. Alternatively, small amine molecules, specifically hydrazine and / or ethylenediamine, can also be used. Primary amines in amine chain extenders exhibit high reactivity with isocyanates, forming polyurethane ureas. These are usually added during the polyurethane emulsification and dispersion stage. Due to the strong polarity of the urea group, the synthesized polyurethane material possesses excellent adhesion and heat resistance.

[0024] The hydrophilic chain extender is 2,2-dimethylolpropionic acid, which provides sufficient carboxyl groups in a small amount.

[0025] Salt-forming agents can neutralize the low-activity carboxyl groups retained by hydrophilic chain extenders to yield ammonium or alkali metal salts, thereby increasing the hydrophilicity of the molecular chain. Furthermore, when triethylamine is used as the salt-forming agent, the synthesized polyurethane material exhibits strong stability.

[0026] The double bond end-capping agent is hydroxyethyl methacrylate (HEMA). The grafting content of HEMA determines the content of acrylate molecules, which in turn affects the viscosity and physical properties of the adhesive layer. As the grafting content increases, the emulsion particle size decreases, the surface tension of the emulsion decreases, the wetting ability improves, and both water resistance and adhesion are enhanced. Microscopically, as the grafting content of the end-capping agent HEMA increases, more acrylate molecules are linked to the polyurethane molecular chains, resulting in better compatibility between the two.

[0027] Preparation method: Polycarbonate diol (industrial grade, Mn=2000) and isophorone diisocyanate IPDI (content ≥99%) were mixed at a molar ratio of 1:1.2. 0.3–0.6 wt% dibutyltin disilicate (DBTDL) catalyst was added dropwise, and the reaction temperature was maintained at 80±1℃ for 1 h. Then, a hydrophilic chain extender solution of 2,2-dimethylolpropionic acid (DMPA) (content ≥98%) with a mass ratio of 0.3:1 to IPDI was added, and the reaction was continued. The reaction was carried out at 80±1℃ for 1 h; then 1,4-butanediol (BDO) chain extender with a mass ratio of 0.14:1 to IPDI was added to prepare a prepolymer; the temperature was lowered to 42℃, and hydroxyethyl methacrylate (HEMA) double bond end-capping agent with a molar ratio of 0.42:1 to the remaining -NCO was introduced, followed by the addition of triethylamine (TEA) salting agent to neutralize to a pH of 7-8. Under high-speed stirring, second deionized water was added for emulsification to obtain an aqueous acrylic polyurethane emulsion.

[0028] acrylic polymer monomers

[0029] The polymer comprises isooctyl acrylate, methyl methacrylate, and 4-acryloylmorpholine in a mass ratio of (70–80):(3–5):(3–5). Isooctyl acrylate (2-EHA) imparts good flexibility, elasticity, and toughness to the polymer, contributing to improved hydrolytic stability and adhesion to various substrates in waterborne polyurethanes. Methyl methacrylate (MMA) provides relatively rigid polymer chains, thereby increasing the hardness and modulus of the final product. Compared to acrylate monomers, polymers formed with MMA exhibit better thermal stability and UV resistance, and significantly enhance the polymer's mechanical strength and abrasion resistance. 4-Acryloylmorpholine (ACMO), as a functional monomer, can introduce nitrogen atoms during polymerization, which facilitates hydrogen bonding or reactions with other functional groups, promoting the formation of cross-linked networks and improving the polymer's high-temperature resistance. The amide group in ACMO can enhance the polymer's hydrophilicity, making it easier to disperse in water and improving the stability of the coating slurry.

[0030] Flame retardant modified polymers

[0031] It is prepared by catalytic polymerization of a first polyisocyanate and a first polyol, wherein the first polyol comprises a hydroxyl-terminated unsaturated polyether and a hydroxyl-containing flame-retardant monomer. The first polyisocyanate is isophorone diisocyanate (IPDI).

[0032] Preparation of hydroxyl-terminated unsaturated polyether: 1,3-propanediol and potassium hydroxide were added to a reactor, followed by glycidyl methacrylate. The reaction was carried out under vacuum at 75-85°C to obtain hydroxyl-terminated unsaturated polyether. The molar ratio of 1,3-propanediol to glycidyl methacrylate was 1:(4-5), and the amount of potassium hydroxide added was 5%-6% of the amount of 1,3-propanediol added.

[0033] Preparation of hydroxyl-containing flame retardant monomers: 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) and 4,4'-dihydroxybenzophenone (DHBP) were mixed and added in a reactor under a nitrogen atmosphere at a molar ratio of 5.5:1, heated to 180℃, reacted for 4 hours, and then purified by filtration.

[0034] The flame retardant modified polymer was prepared by mixing hydroxyl-containing flame retardant monomers and hydroxyl-terminated unsaturated polyethers in a molar ratio of 1:(0.5-0.8), and first polyisocyanate (IPDI) and first polyol in a molar ratio of 2.1:1, dissolving them in acetone, and then adding 0.4-0.6 wt% dibutyltin disterol silicate (DBTDL). The hydroxyl-containing flame retardant monomers were first reacted with IPDIs, and the reaction was carried out with thorough stirring at 65°C for 36 h. Then, the hydroxyl-terminated unsaturated polyethers were added dropwise until the remaining -NCO content in the solution was less than 0.5 wt.% of the total reactants.

[0035] Modified magnesium-aluminum hydrotalcite

[0036] The modified magnesium-aluminum hydrotalcite matrix is ​​prepared from magnesium salts, aluminum salts, sodium alginate, and basic alcohol compounds in a mass ratio of (1.5–2.5):1:(0.05–0.06):(45–50). If the magnesium salt content is too low, the hydrotalcite morphology is irregular; if the magnesium salt content is too high, the basic growth unit of the matrix changes from multilayer stacking to single-layer, which is not conducive to the multiple refractions of incident light in the porous structure of the modified magnesium-aluminum hydrotalcite to reduce reflectivity. The porous bud-like structure induced by sodium alginate facilitates multiple refractions of incident light in the porous structure of the modified magnesium-aluminum hydrotalcite to reduce reflectivity, thereby enhancing the spectral absorption of the composite tarpaulin in the visible-near-infrared range.

[0037] Magnesium salts include, but are not limited to, magnesium nitrate, magnesium chloride, magnesium sulfate, and their hydrates. Further, magnesium salts include magnesium nitrate hexahydrate.

[0038] Aluminum salts include, but are not limited to, aluminum nitrate, aluminum chloride, aluminum sulfate, and their hydrates. Further, an aluminum salt is magnesium nitrate hexahydrate.

[0039] Alcohols include, but are not limited to, one or more of methanol, ethanol, and propanol. Further, the alcohols are methanol and / or ethanol.

[0040] The olefinic unsaturated monomer includes, but is not limited to, one or more of acrylic acid, methacrylic acid, and maleic acid. Further, the olefinic unsaturated monomer is acrylic acid.

[0041] Preparation of modified magnesium-aluminum hydrotalcite: A basic alcohol compound was prepared by mixing NaOH solid (weight ratio 1:5.8) and a first portion of methanol at 50°C. At room temperature, magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, and a second portion of methanol were mixed to obtain a first reaction solution. At 50°C, the basic solution was slowly added dropwise to the reaction solution while stirring at 3200 r / min until the pH reached 8. The addition was stopped, and the reaction continued for 24 h. Sodium alginate was then added, and the temperature was raised to 120°C for 6 h. After cooling, a second reaction solution containing a magnesium-aluminum hydrotalcite matrix was obtained. The second reaction solution was heated to 60°C, and sodium dodecylbenzenesulfonate was added and stirred for at least 15 h until a gel-like substance was obtained. The gel-like substance was repeatedly washed with methanol solvent for later use. A first mixture was prepared by adjusting the pH to neutral using acrylic acid, water, and a strong alkali. This first mixture was heated to 40°C and mixed with the washed gel-like substance, and the reaction was stirred for at least 20 h.

[0042] The prepared gel contains M-OCH3 groups that readily hydrolyze to generate M-OH. The hydrolysis reaction is rapid and vigorous, and the energy released by the reaction can break down the gel into tiny particles. These tiny particles can be suspended in the aqueous solution. During the process of methanol molecules formed by hydrolysis detaching from the layers, the interaction between the main layers weakens, promoting the interlayer ion exchange reaction between acrylate anions and dodecyl sulfonate anions. This process prepares a layered intercalated hydrotalcite-like compound with olefinic unsaturated groups. The modified magnesium-aluminum hydrotalcite particles are further suspended in the aqueous solution by the emulsification effect of free dodecyl sulfonate ions.

[0043] Modified magnesium-aluminum hydrotalcite crosslinks with other raw materials in the coating slurry through unsaturated bonds, preventing the reduction of infrared stealth effect after long-term use. In addition, modified magnesium-aluminum hydrotalcite has flame retardant properties, and when compounded with flame retardant modified polymers, it improves the flame retardant effect of the coating slurry.

[0044] The mixture contains 20 parts of a second reaction solution with a magnesium-aluminum hydrotalcite matrix, 10 parts of sodium dodecylbenzenesulfonate, and 3 parts of acrylic acid.

[0045] Example 1

[0046] By weight, the coating slurry for tarpaulins comprises 100 parts of water-based acrylic polyurethane, 18 parts of acrylic polymer monomers, 13 parts of flame retardant modified polymers, 12 parts of modified magnesium-aluminum hydrotalcite, 3 parts of emulsifiers, 1.5 parts of initiators, and 130 parts of first deionized water.

[0047] The flame-retardant modified polymer was obtained by the above preparation method, wherein the molar ratio of hydroxyl-terminated unsaturated polyether to hydroxyl-containing flame-retardant monomer was 0.6:1. The modified magnesium-aluminum hydrotalcite was obtained by the above preparation method, wherein the mass ratio of magnesium salt, aluminum salt, sodium alginate, and basic alcohol compound was 2.1:1:0.054:48. The acrylic polymer monomers included isooctyl acrylate, methyl methacrylate, and 4-acryloylmorpholine in a mass ratio of 76:4:4. The emulsifier was octylphenol polyoxyethylene ether (OP-10), and the initiator was an aqueous solution of potassium persulfate.

[0048] The composite tarpaulin includes a substrate layer having a first surface and a second surface opposite each other along the layer thickness. A functional coating is disposed on the first surface, and the functional coating is obtained by drying the aforementioned tarpaulin coating paste. The tarpaulin is made of polyester fiber, and the thickness of the functional coating is 135 μm.

[0049] Example 2

[0050] Example 2 is based on Example 1, except that, by weight, the coating slurry for tarpaulins includes 100 parts of waterborne acrylic polyurethane, 18 parts of acrylic polymer monomers, 10 parts of flame retardant modified polymer, 15 parts of modified magnesium-aluminum hydrotalcite, 3 parts of emulsifier, 1.5 parts of initiator, and 130 parts of first deionized water. All other components remain unchanged.

[0051] Example 3

[0052] Example 3 is based on Example 1, except that, by mass parts, the coating slurry for tarpaulin includes 100 parts of waterborne acrylic polyurethane, 10 parts of acrylic polymer monomer, 13 parts of flame retardant modified polymer, 12 parts of modified magnesium aluminum hydrotalcite, 3 parts of emulsifier, 1.5 parts of initiator, and 130 parts of first deionized water, with the rest remaining unchanged.

[0053] Example 4

[0054] Example 4 is based on Example 1, except that, by mass parts, the molar ratio of hydroxyl-terminated unsaturated polyether to hydroxyl-containing flame-retardant monomer in the flame-retardant modified polymer is 1:1. Other components remain unchanged.

[0055] Comparative Example 1

[0056] Comparative Example 1 is based on Example 1, except that the flame retardant modified polymer in the coating slurry for the tarpaulin is polytetrahydrofuran diol (Mn = 2000), and the polytetrahydrofuran diol is a saturated polyether alcohol. Other components remain unchanged.

[0057] Comparative Example 2

[0058] Comparative Example 1 is based on Example 1, except that the coating paste for the tarpaulin does not include the flame-retardant modified polymer. All other components remain the same.

[0059] Performance testing:

[0060] 1. Flame retardancy: Tested according to standard GB / T 17591-2006 "Flame Retardant Fabrics";

[0061] 2. Infrared absorption performance: Lambda 750 UV / Vis / NIR spectrophotometer. The lower the reflectance, the better the absorption of infrared radiation and the better the stealth effect. Continuous measurement is performed after the sample has been washed with water 100 times.

[0062] 3. Aging resistance: The test chamber is set at 70°C for half a month.

[0063] The test results for the examples and comparative examples are as follows:

[0064]

[0065] Compared to Example 1, Example 2 has a lower content of flame retardant modified polymer, which has a negative impact on the abrasion resistance of the tarpaulin, a lower high-temperature resistance, and a negative impact on the adhesion stability of the coating in water washing and aging tests.

[0066] Compared to Example 1, Example 3 has a lower content of acrylic polymer monomers, which reduces the adhesion of the coating and has a negative impact on the flame retardancy and infrared absorption performance of the tarpaulin after washing.

[0067] Compared to Example 1, Comparative Example 1 showed that the flame retardant-modified polymer did not contain unsaturated bonds that participated in cross-linking. After repeated washing of the tarpaulin, the flame retardant was prone to migration, which had a negative impact on the flame retardancy. The cross-linking density of the coating was also reduced, which had a negative impact on the aging resistance and infrared absorption performance of the tarpaulin.

[0068] Compared to Example 1, Comparative Example 2, which combines flame retardant-modified polymers and modified magnesium-aluminum hydrotalcite, produces tarpaulins with superior flame retardancy and infrared absorption properties.

[0069] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the technical principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A coating slurry for tarpaulin, characterized in that: It includes water-based acrylic polyurethane, acrylic polymer monomer, flame retardant modified polymer, modified magnesium aluminum hydrotalcite, emulsifier, initiator and first deionized water; The flame retardant modified polymer is prepared by catalytic polymerization of a first polyisocyanate and a first polyol, wherein the first polyol comprises a terminal hydroxyl unsaturated polyether and a hydroxyl-containing flame retardant monomer.

2. The coating slurry for tarpaulin according to claim 1, characterized in that: The coating slurry comprises, by weight, 100 parts of aqueous acrylic polyurethane, 15-20 parts of acrylic polymer monomers, 10-15 parts of flame retardant modified polymers, 10-15 parts of modified magnesium aluminum hydrotalcites, 2-4 parts of emulsifiers, 1-2 parts of initiators and 100-150 parts of first deionized water.

3. The coating slurry for tarpaulin according to claim 1 or 2, characterized in that: The waterborne acrylic polyurethane is prepared from a second polyol, a second polyisocyanate, an alcohol and / or amine small molecule chain extender, a hydrophilic chain extender, a double bond end-capping agent, a salt-forming agent and a second deionized water, wherein the second polyol is one or more of polytetramethylene glycol, poly-ε-caprolactone glycol and polycarbonate glycol.

4. The coating slurry for tarpaulin according to claim 3, characterized in that: The double bond capping agent is hydroxyethyl methacrylate, and the grafting content of the double bond capping agent in the waterborne acrylic ester polyurethane is 40% to 45%.

5. The coating slurry for tarpaulin according to claim 1 or 2, characterized in that: The hydroxyl-containing flame retardant monomer is synthesized from 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) and 4,4'-dihydroxybenzophenone (DHBP).

6. The coating slurry for tarpaulin according to claim 5, characterized in that: The molar ratio of the terminal hydroxyl unsaturated polyether to the hydroxyl-containing flame retardant monomer is (0.5-0.8):

1.

7. The coating slurry for tarpaulin according to claim 1 or 2, characterized in that: The modified magnesium-aluminum hydrotalcite is a layered hydrotalcite compound with olefinic unsaturated groups. The magnesium-aluminum hydrotalcite matrix in the modified magnesium-aluminum hydrotalcite is prepared from magnesium salt, aluminum salt, sodium alginate and alkaline alcohol compound in a mass ratio of (1.5-2.5):1:(0.05-0.06):(45-50).

8. The coating slurry for tarpaulin according to claim 1, characterized in that: The acrylic polymer monomers include isooctyl acrylate, methyl methacrylate and 4-acryloylmorpholine in a mass ratio of (70-80):(3-5):(3-5).

9. The coating slurry for tarpaulin according to claim 1, characterized in that: The emulsifier is one or more of octylphenol polyoxyethylene ether (OP-10), Span, Tween, and 12-alkyl sodium sulfonate, and the initiator is potassium persulfate and / or ammonium persulfate aqueous solution.

10. A composite tarpaulin, comprising a substrate layer, wherein the substrate layer has a first surface and a second surface opposite to each other along the thickness of the layer, characterized in that: The first surface and / or the second surface is provided with a functional coating, and the functional coating is obtained by drying the coating slurry for the tarpaulin according to any one of claims 1 to 9.